Surgical outcomes for hepatocellular carcinoma detected after hepatitis C virus eradiation by direct‐acting antivirals. Issue 8 (27th August 2020) - Tanaka, Shogo; Shinkawa, Hiroji; Tamori, Akihiro; Takemura, Shigekazu; Takahashi, Shinji; Amano, Ryosuke; Kimura, Kenjiro; Ohira, Go; Kawada, Norifumi; Kubo, Shoji
Abstract: Objective: To investigate the postoperative recurrence of hepatitis C virus (HCV)‐related hepatocellular carcinoma (HCC) after liver resection in patients with and without the achievement of sustained virologic response (SVR) through the administration of direct‐acting antivirals (DAA). Methods: Among 28 patients with HCC detected after DAA‐SVR (DAA group) and 197 patients with HCC who did not receive treatment for HCV infection or who did not achieve an SVR (control group) between January 2000 and July 2019, we performed propensity score matching (PSM) to avoid confounding differences between the two groups. Results: After PSM, 28 patients in each group were selected for analysis. The DAA‐SVR patients showed improved liver function at operation and at recurrence in comparison to the control group. The disease‐free survival rate at 3 years after surgery was 69% in the DAA group and 35% in the control group, respectively ( P  = .021). In the DAA group, all three patients with recurrence met the Milan criteria and could be managed by curative treatments and none died of liver failure during the follow‐up period. Conclusions: SVR status suppresses postoperative recurrence of HCV‐related HCC detected after DAA‐SVR. Improved liver function may contribute to the successful treatment and prevention of liver failure.